Hukum Administrasi Negara Bidang Ketenagakerjaan Zaman Orde Baru, Era Reformasi Dan Era Digitalisasi Dalam Revolusi Industri 4.0. - Dewi Oktavia; Junaedi; Sugeng Prayitno (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This paper discussed the development of State Administrative Law in the field of employment from the New Order era to the era of digitalization and the Industrial Revolution 4.0. The paradigm shift of the night watchman state to field-based functions, such as Homeland Security and Administrator Welfare, affects state intervention in the private lives of citizens. The HAN aims to regulate government activities and create welfare for its people. The loss of the governor's authority in setting sectoral minimum wages was a result of the Job Creation Law, which led to a number of lawsuits in the State Administrative Court. During the New Order era, the Minister of Manpower set the wage policy, while the reform era brought significant changes in the government order, including the governor's authority in setting sectoral minimum wages. However, in the era of digitalization and Industrial Revolution 4.0, the Job Creation Law gives the governor full authority to set minimum wages, with direct impact on administrative decisions. In conclusion, HAN in the field of labor has not shown significant progress in developing the interests of citizens. In the reform era, the silence of state administrative officials is interpreted as approval, while the concept of omnibus law in legislation has an impact on the limited authority of government agencies and officials. State Administration Law Number 30 of 2014 is the legal basis for state administration in a substantive sense, while labor laws have a close relationship with HAN, especially regarding the determination of minimum wages.